Aplikasi Pencatatan Poin Pelanggaran Siswa Berbasis Mobile Pada SMK Advent Batam - Darmawan, Justin; Callista, Sentia; Yamin, Valerian; Fery (Journal of Digital Ecosystem for Natural Sustainability, 2024)
This research focuses on developing a mobile application for recording and monitoring student violations at SMK Advent Batam, addressing the inefficiencies and errors of the current manual system. Using the Waterfall model and developed with Dart and the Flutter framework, the application integrates with a MySQL database to enable teachers and staff to easily input and verify violations. The app also provides parents with real-time access to their children's records, improving communication and transparency. Testing confirmed that the system enhances efficiency, accuracy, and accessibility, offering a more reliable solution for managing student violations and supporting decision-making processes.